Gaya Arsitektur Rumah Istri Sultan Amaluddin Tengku Khalijah di Kota Maksum - Zuhdi, Hafiz; Siregar, Yusra Dewi (Jayapangus Press, 2024)
Kota Maksum is an elite area that was once the residence of the nobles of the Deli Sultanate since the royal family moved from the palace in Labuhan to the Maimun Palace in 1891. The development of Kota Maksum was inseparable from the collaboration between the kingdom and the Dutch colonialists at that time so that the buildings of the Sultanate Many Delis were built by Dutch architects, including the Kota Maksum area. One proof of the legacy of the residence of the Deli nobles in Maksum City today is the house of Sultan Amaluddin Tengku Khalijah's wife. This house is the residence of Tengku Khalijah, the wife of Sultan Amaluddin Sani Perkasa Alamsyah, located in Maksum City. What's unique is that this house still stands strong today, even though it looks like the house is not very well maintained. In this way, the author immediately plunged into the field to see the house. This research aims to reveal the architectural style and ornaments used in the house of Sultan Amaluddin Tengku Khalijah's wife in Maksum City. The research method used in this research is a historical approach using data collection techniques through field observations, direct interviews with Tengku Khalijah's descendants, and literature study. The findings from this research show that Tengku Khalijah's house is structurally styled using Dutch colonial architecture which can be seen in elements such as stiles, doors, windows, dormer roofs, roof peak decoration and the use of the dominant color white in the house which is generally also used. on Other Colonial houses. Several typical Malay ornaments with floral motifs are also used in this house.